GERMAN ENTRIES IN KAMUS BESAR BAHASA INDONESIA V - Wulandari, Julia; Kiasati, Shabrina Nabila (UI Scholars Hub, 2019)
Kamus Besar Bahasa Indonesia (KBBI) is an official Indonesian defining/monolingual dictionary. In the KBBI V offline language features, there are 27 German entries have been absorbed into Indonesian. Hence, this research focuses to analyse which German entries contained in KBBI V, does the lexical meaning of those entries in KBBI V differ from the German defining dictionary, and what characters of Germany is represented in those entries. This research applies qualitative method, and the lexical meaning of the 27 German entries in the KBBI V are compared to the German defining dictionary as the ground to analyse the experience alteration. Furthermore, this paper examines the characters of the Germany appear in those entries and what their importance to Indonesian. The results of the research demonstrate that there are semantics shifting and narrowing of those German entries in KBBI V compared to the German monolingual dictionary, caused by a change in the concept of words related to the meaning of the words in a reference, associative, and contextual manner. Another result indicates a change occurs in the fields of German history, politics, and philosophy strengthening the characters of Germany which grow and widely known in Indonesia.